Cooperation in the System «University - School» as a Prerequisite of Effective Organization and Conduct of Pedagogical Practice - Nataliia Kazakova (Pedagogical Discourse, 2017)
As part of the implementation of the concept «New Ukrainian School», the issue of cooperation between school and higher educational institutions is relevant. The secondary school prepares the ground for the future teachers to become not only highly skilled specialists in their field, but also educated people. Therefore, there is an urgent need to change the approaches, content, forms and methods of interaction of teachers of all levels of the education system, which enables them to combine their knowledge, skills, abilities and experience to effectively solve the pressing problems of education and to increase their professionalism. The attention is paid to the fact that pedagogical practice is an important component of the professional training of the future teachers, which contributes to the formation of a competitive, highly intellectual, innovative specialist, able to build his or her own trajectory of professional development, ready for variability in pedagogical activity. One of the necessary conditions for the organization of pedagogical practice of students is the cooperation of a higher educational establishment and practice bases, which will allow successful realization of its purpose. The goals and directions of cooperation of universities with the bases of practice have been considered. The effective forms of such interaction under the present conditions (from the experience of work of Khmelnytskyi Humanitarian-Pedagogical Academy) have been offered. It is emphasized that the expected results of cooperation between universities and schools should facilitate the organization and conduct of competence-oriented pedagogical practice of students and provide for the formation of the professional and pedagogical competence of the future teachers in order to ensure the diverse development, education and socialization of the personality of a pupil, who realizes himself or herself as a citizen of Ukraine, capable of life in the society and civilized interaction with nature, has a desire for self-improvement and learning throughout life, ready for consciousness life choices and self-realization, labour and civil activity.